Spatial variation of land use carbon budget and zoning for carbon compensation in the Huai River Eco-economic Belt, China - Hongwen Xu; Xiaorui Tao; Yan Lu; Yuexiang Wang; Hui Li; Zhengwei Ye (Scientific Reports)
Abstract Carrying out carbon budget assessment and carbon compensation zoning research from inter-regional perspective can actively boost the formulation of green, low-carbon transformation strategies, guiding the flow of compensation credits, promoting regional equity and sustainable development, and realizing China’s “dual-carbon” goal. Huai River Eco-economic Belt is considered to be a typical example of how land use affects carbon budget due to its more drastic land changes. The paper uses the carbon emission coefficient method to analyze the carbon revenue and expenditure of kinds of land-use patterns, and constructs the carbon compensation model with the help of the carbon budget concentration index and the dominant comparative advantage index, and puts forward the carbon compensation zoning program. Results indicate that (1) Carbon emissions in the Huai River Eco-economic Belt are generally showing a downward trend, and carbon absorption rises modestly. (2) Carbon emissions exhibit a spatial distribution of higher in the western, northern and eastern regions and lower in the center zone, with large differences in carbon absorption among cities in the same year. (3) Carbon compensation types in the Huai River Eco-economic belt include 7 payment zones, 5 balanced zones and 14 compensated zones, which can be finally classified into 5 categories of carbon compensation space optimization areas by combining with the Normalized Revealed Comparative Advantage Index and model for zoning of carbon compensation. Our study enriches practical approaches to reducing carbon emissions through land regulation from inter-regional scales.